Analisis Dampak Adiksi Internet terhadap Kualitas Tidur pada Mahasiswa Kesehatan Masyarakat UPN Veteran Jakarta selama Pembelajaran Daring Tahun 2021 - Rizky Putri Amelia (2021)
Internet addiction continues to increase during the pandemic which can cause sleep disturbances, this is because the internet, especially social media, is used as a recreational medium during the pandemic and can be accessed late at night by teenagers. The purpose of this study was to analyze the impact of internet addiction on sleep quality on UPN Veteran Jakarta Public Health students during online learning in 2021. This study used a Cross Sectional approach with a research sample of 221 people. The research instrument used was the Internet Addiction Test (IAT) questionnaire and the Pittsburgh Sleep Quality Index (PSQI). The analysis of the results of this study is univariate analysis and bivariate analysis using Chi Square and Logistic Regression. The results of the analysis show that internet addiction has an impact on sleep quality, where the p-value for moderate internet addiction is 0.001 and the p-value for severe internet addiction is 0.000 (p-value <0.05). With the impact of internet addiction on sleep quality, students are advised to start scheduling and controlling internet usage, start looking for activities in real life, and not access the internet at least 30 minutes before going to bed.